METHODICAL APPROACHES TO CASH FLOW MANAGEMENT IN THE FRAMEWORK OF CORPORATE TYPE VALUE ASSESSMENT - Артимоновая, Ирина; Герасименко, Ирина; Гутко, Людмила (SWorldJournal, 2020)
The article considers analytical indicators of cash flow management of a corporate enterprise. The main methods of determining the discount rate with justification of their feasibility in assessing the value of corporate-type enterprises are analyzed. It